LEGAL AND ECONOMIC BASIS OF PROTECTION OF PEOPLE WITH DISABILITIES DURING MARITAL STATE - Prypkhan , I. I.; Shchur , R. I.; Solodzhuk , T. V. (The actual problems of regional economy development, 2024)
The article examines the system of legislation that regulate the legal and economic basis of protection of persons with disabilities during martial law. The full-scale war, which has been going on in Ukraine for the third year, is a determining factor that reduces the quality of life of ordinary citizens of Ukraine, and also negatively affects the economy of our country. According to the Ministry of Reintegration of the Occupied Territories of Ukraine, during the year and a half of the war, the number of people with disabilities increased by 300,000 compared to the pre-war period. Such people need a wider list of forms of social protection, the financing of which cannot be provided at the expense of the financial resources available to the state, as well as improvement the system of their legal protection. The purpose of the article is to study the legal and economic foundations of the protection of disabled people’ rights during martial law. The article establishes that the main task and at the same time the duty of the state is to create conditions for realizing the rights of persons with disabilities and ensuring their social protection, eliminating or compensating the consequences caused by the presence of a disability, functioning of the system for supporting their social inclusion and assisting them in achieving social and material independence. Fulfillment of this task involves the creation by the state of legal, economic, political, social, psychological and other conditions for the realization of their rights and opportunities on an equal basis with other citizens to participate in public life. This includes measures related to: removing obstacles and barriers, forming a society with a high level of social inclusion, which provides access to the objects of the physical environment and opportunities for personal development; health care; ensuring the implementation of an individual rehabilitation program for persons with disabilities; provision of adapted housing; promotion of public activities; individual program of psychological and pedagogical, labor, physical culture and sports, social rehabilitation and adaptation of such persons.